Hierarchical document representation for summarization - Tey, Rui Jie (Nanyang Technological University, 2022)
Most extractive summarization models usually employ a hierarchical encoder for document summarization. However, these extractive models are solely using document-level information to classify and select sentences which may not be the most effective way. In addition, most state-of-the-art (SOTA) models will be using huge number of parameters to learn from a large amount of data, and this causes the computational costs to be very expensive.